Public service and civil society: issues of interaction - N. A. Shkarina (Путеводитель предпринимателя)
The author considers the existing problems of interaction between the public service and civil society, directions and ways to increase the effectiveness of this interaction. The improvement of the system and mechanism of interaction between the State and civil society will solve the existing problems in this field and will have a direct impact on the implementation and development of the whole range of human and civil rights and freedoms.